Field observations of seabed scour dynamics in front of a seawall during winter gales - Sun, Hongan; Xu, Jishang; Zhang, Shaotong; Li, Guangxue; Liu, Shidong; Qiao, Lulu; Yu, Yue; Liu, Xingmin (Frontiers in Marine Science, 2022)
Seawalls are vital for protecting coastal areas. However, the seabed in front of seawalls may undergo severe scouring. This can result in destabilization of the seawall structure, the underlying mechanisms of which remains unclear. Therefore, an integrated observation system consisting of acoustic and optical instruments was deployed in areas with severe seabed scouring. This observation system was used to observe sediment dynamics elements such as waves, currents, tides, turbulence and suspended sediment concentration (SSC) for 31 days in winter. Using advanced time–frequency analysis techniques including wavelet transform and spectrum analysis, we examined the dynamic factors associated with sediment resuspension and transport. In calm weather conditions, a notable increase in SSC was not observed indicating that the tidal dynamics were not sufficient for sediment suspension. During high winds, the SSC increased sharply to 12,222 mg/L, and the sediment vertical diffusion flux induced by turbulence was coupled to SSC, indicating that the increased SSC was predominantly attributed to local resuspension. Consistent temporal distribution of turbulence-induced sediment vertical diffusion flux and momentum flux in high wavelet power spectra highlights the important role of turbulence in sediment dynamics. Enhanced longshore currents during high wave conditions intensified sediment transportation. Horizontal net sediment fluxes notably increased to 769 t/m2 per day during winter gales, which had a significant effect on seabed erosion. This study reveals the key processes associated with seabed scouring in front of seawalls during gale events.